Psikoedukasi Psychoeducation in Increasing Knowledge about Bullying at State Senior High School 11 Padang - Rozi Sastra Purna; Fitri Angraini (Warta Pengabdian Andalas, 2024)
School-age children are very susceptible to cases of bullying. Bullying is a form of aggressive behavior that is carried out repeatedly by physically or mentally hurting someone; it could be carried out by a child or a group of children against other children. Bullying behavior has a negative and detrimental impact not only on victims but also on perpetrators. This impact is not only felt during the period when bullying behavior occurs but can continue until the perpetrator and victims enter adulthood. Based on preliminary data from interviews and observations at State Senior High School 11 Padang City, several cases of bullying were found between seniors and juniors or classmates. Some of the behaviors identified were calling friends bad names, threatening them, and making fun of them. As a result, victims experience anxiety and fear and even lose their confidence in participating in school activities. It is hoped that psychoeducation can be an intervention to increase students' knowledge of bullying behavior. Psychoeducation is carried out face-to-face in the hall. The material provided includes types of bullying behavior, the negative impacts of bullying, their roles and strategies, and what needs to be done when they see bullying. Psychoeducation was given to 347 students who took part in P5 phase F. The research method used in the study is a one-group pretest-posttest design. The results of the analysis carried out using the Wilcoxon test showed that there was a significant increase in scores before and after psychoeducation was carried out. It showed that psychoeducation was quite effective in improving students' understanding of bullying.